2017
DOI: 10.1177/0021998317726147
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability and adhesive strength of boron nitride nano platelets and carbon nano tube modified adhesives

Abstract: The effect of multi-walled carbon nanotube and/or boron nitride nano platelets usage on shear strength and thermal stability of epoxy based adhesives have been investigated. Commercially available diglycidyl ether of bisphenol A based epoxy was used as matrix and reinforced by using nanofillers. The resulting adhesive was tested for its shear-lap adhesion to aluminum alloy sheets (2024-T3). The nano particles modified epoxy adhesives were characterized by Fourier transform infrared, differential scanning calor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
(37 reference statements)
0
5
0
Order By: Relevance
“…20 As a result, some studies have modified the surface of BN in an effort to improve the dispersion and decrease the surface thermal resistance of polymeric composites. 21,22 For instance, Ryu et al 23 modified BN platelets by 3-aminopropyl triethoxysilane (KH550) (BN-KH550) to enhance the thermal conductivities of polyethylene naphthalate (PEN) composites. Their data showed the λ value of PEN composite filled with 50 wt% BN-KH550 platelets reached 1.63 W/mK, a value of 16% higher than that of 50 wt% BN/PEN composite (1.41 W/mK).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…20 As a result, some studies have modified the surface of BN in an effort to improve the dispersion and decrease the surface thermal resistance of polymeric composites. 21,22 For instance, Ryu et al 23 modified BN platelets by 3-aminopropyl triethoxysilane (KH550) (BN-KH550) to enhance the thermal conductivities of polyethylene naphthalate (PEN) composites. Their data showed the λ value of PEN composite filled with 50 wt% BN-KH550 platelets reached 1.63 W/mK, a value of 16% higher than that of 50 wt% BN/PEN composite (1.41 W/mK).…”
Section: Introductionmentioning
confidence: 99%
“…Organic rhodanine (Rd) is a rubber-curing accelerator derived from thiazolidine. The large amounts of accepting structure (N C═S) in Rd, which can tautomerize to yield N═thiazolidine, 22 could allow rapid Rd reaction with sulfur and transformation into inactive crosslinking precursors. 26 Some recent studies have suggested that Rd may undergo self-polymerization to form polyrhodanine (PRd) shells on nanoparticles, thereby producing core-shell structured nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were described by Ulus et al . where small proportions of CNTs result in better mechanical behaviour than when increasing the concentration of nanofillers . On increasing the CNT content, the viscosity of the formulation becomes higher and the possibility of the formation of agglomerates increases, which influences the processing and the final properties .…”
Section: Resultsmentioning
confidence: 99%
“…Hybrid PU composites are used in the literature because of improved properties such as bridging the gap, crack blunting, crack propagation and arrest, thermal and electrical conductivity. [25][26][27][28] In this study, 0.5% by weight Boron Nitride Nanoplates (BNNP) and/or 0.25%, 0.35, and 0.45% by weight Multi-walled Carbon Nanotubes (MWCNT) reinforced polyurethane (PU) nanocomposites were mixed by solution casting method, and according to ASTM D638-10 and ASTM D790-02 tensile and flexure, specimens were produced.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid PU composites are used in the literature because of improved properties such as bridging the gap, crack blunting, crack propagation and arrest, thermal and electrical conductivity. 25-28…”
Section: Introductionmentioning
confidence: 99%